Within‐Boll Yield Characteristics and Their Correlation with Fiber Quality Parameters following Mutagenesis of Upland Cotton, TAM 94L‐25. Issue 4 (1st July 2015) - Brown, Nino; Smith, C. Wayne; Hague, Steve; Auld, Dick; Hequet, Eric; Joy, Kolbyn; Jones, Don
ABSTRACT: Limited genetic diversity could be contributing to the limited genetic gains in upland cotton, G ossypium hirsutum L., fiber lengths and strengths. Smith and Coyle (1997) reported negative associations between many fiber quality traits and the number of fibers per unit surface area of seed (FSSA), the most basic lint yield component. The objective of this study was to determine if mutagenesis could be used to modify the associations of within‐boll yield components and fiber quality parameters. TAM 94L‐25 (Smith, 2003) (PI 631440) seeds were treated with 3% v/v ethyl methanesulfonate (EMS). Twelve TAM 94L‐25 M4:6 mutant (M) lines, 'FiberMax FM 832' (Constable et al., 2001) (PVP 9800258; PI 603955) and 'Phytogen PSC 355' (PI 612974), and the unmutated parent TAM 94L‐25 were grown in performance trials in 2008 and 2009. The data suggests EMS‐based mutagenesis was successful in producing variation for within‐boll yield characteristics as well as fiber quality. Whether or not linkages or pleiotropic effects were disrupted is equivocal, with some correlation values significantly different between the control cultivars and the M lines. Mutant lines M2, M3, M50, and M51 were identified with improved FSSA. Ethyl methanesulfonate–based mutagenesis could be a valuable additional tool to create selectable variation in cotton for basic lint yield components and to break linkages of basic yield components and fiber quality.